2015
DOI: 10.1292/jvms.14-0496
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of arylacetamide deacetylase in cynomolgus macaques

Abstract: Arylacetamide deacetylase (AADAC), a microsomal serine esterase, hydrolyzes drugs, such as flutamide, phenacetin and rifampicin. Because AADAC has not been fully investigated at molecular levels in cynomolgus macaques, the non-human primate species widely used in drug metabolism studies, cynomolgus AADAC cDNA was isolated and characterized. The deduced amino acid sequence, highly homologous (92%) to human AADAC, was more closely clustered with human AADAC than the dog, rat or mouse ortholog in a phylogenetic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…This finding was consistent with the amino acid profile showing high similarity with the CCL7 sequence in M. nemestrina (98%) and human (92%) compared to rodents (±70%) (Table 1). Our findings are consistent with previous studies on other genes and proteins which reported a high similarity between M. fascicularis and humans at the molecular level (Ogawa and Vallender 2014;Uno et al 2015).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding was consistent with the amino acid profile showing high similarity with the CCL7 sequence in M. nemestrina (98%) and human (92%) compared to rodents (±70%) (Table 1). Our findings are consistent with previous studies on other genes and proteins which reported a high similarity between M. fascicularis and humans at the molecular level (Ogawa and Vallender 2014;Uno et al 2015).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that M. fascicularis CDS CCL7 consisted of three exons whereas the intron sequence isolated was consistent with the consensus sequence for splice junctions in introns of eukaryotic genes, as it begins with the dinucleotide GU and ends with AG (Uno et al 2015). The 2028 bp sequence of human CCL7 also consists of three exons, whereby 327-460 bp encodes the functional protein.…”
Section: Discussionsupporting
confidence: 69%
“…The observed changes in GSTM isoform levels in the livers of F1 generation females may represent epigenetic changes induced by GLY on the maternal ovary. There were three other drug-metabolizing proteins that were identified as being altered in the ovaries of GLY pre-conceptionally exposed offspring—decreased sulfotransferase (SULT1A1) which is involved in phase II sulfonation ( Pathania et al , 2018 ), increased AADAC which has roles in lipid and drug metabolism ( Jiang et al , 2017 ; Nourbakhsh et al , 2013 ; Uno et al , 2015 ), and decreased TPMT, a phase II chemical biotransformation protein that metabolizes thiopurine substrates ( Hempel et al , 2007 ). These observed GLY-induced alterations could negatively impact the offspring protective response to xenobiotics.…”
Section: Discussionmentioning
confidence: 99%
“…This similarity allows the identification of enzymes from organisms other than model organisms, such as birds, reptiles, or amphibians. Some AADAC orthologues, such as mouse, dog, rat, and cynomolgus macaque AADAC have been studied for their substrate recognition and specificity [11,12,[22][23][24]. For example, human AADAC can hydrolyze flutamide, phenacetin, indiplon, and rifampicin, whereas rat and mouse AADAC only hydrolyzes flutamide and phenacetin, and not rifampicin [11].…”
Section: Introductionmentioning
confidence: 99%
“…Differences in enzyme location are also observed among orthologue AADAC. For instance, in human and cynomolgus macaques, AADAC mRNA is found in the liver and small intestine, whereas in rats and mice, mRNA AADAC is expressed in the kidney [ 22 ].…”
Section: Introductionmentioning
confidence: 99%